Enzyme activity of Ascaridia galli Llarvae was inhibited by Phenil Methanyl Methane Sulfonyl Fluoride - Ummu Balqis; . Darmawi; Muhammad Hambal (Syiah Kuala University, 2011)
Enzyme catalyse a broad spectrum of important biological reactions, including protein metabolism and immune reactions. A study was carried out to partial characterize enzyme from exretory/secretory of A. galli L3 stage based on influence of inhibitor. A. galli L3 were recovered from intestines of 100 heads chickens 7 days after oesophagus inoculation with 6000 L2. L3 recovered in this manner were cultured (5 – 10 ml-1) in flasks containing rosswell park memorial institute (RPMI) 1640 media, pH 6.8, without phenol red. Cultures were incubated at 370C in 5% CO2 and culture fluid was collected after 3 days in culture. Excretory/secretory was prepared from metabolic product of L3 released in culture medium. The enzyme activity was assayed against casein 2%. The amount of concentration was determined from the absorbance at 595 nm. Inhibitor sensitivity on enzyme activity was studied in phenil methanyl methane sulfonyl fluoride (PMSF) 0,5 and 1 mM. The result showed that enzyme activity of A. galli larvae was inhibited by PMSF 0.5 and 1 mM, which enzyme activity remainded 1,8 and 0%, respectively. The results indicate that the excretory/secretory secreted by L3 A. galli contained serine protease